2014
DOI: 10.3389/fpsyg.2014.01253
|View full text |Cite
|
Sign up to set email alerts
|

Character strengths and well-being across the life span: data from a representative sample of German-speaking adults living in Switzerland

Abstract: Character strengths are positive, morally valued traits of personality. This study aims at assessing the relationship between character strengths and subjective well-being (i.e., life satisfaction, positive and negative affect) in a representative sample of German-speaking adults living in Switzerland (N = 945). We further test whether this relationship is consistent at different stages in life. Results showed that hope, zest, love, social intelligence and perseverance yielded the highest positive correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 21 publications
6
52
0
7
Order By: Relevance
“…Character strengths play the role of a cognitive schema, serving to organize categories of information related to oneself, others, and the world [52]. Considerable research findings, including ours, have demonstrated the positive relationship between character strengths and wellbeing across culture, lifespan, and population [25,26,32,53,54]. Given the same conditions, older people with high character strengths likely perceive difficult moments in life in a less negative manner than those with low character strengths.…”
Section: Discussionmentioning
confidence: 75%
“…Character strengths play the role of a cognitive schema, serving to organize categories of information related to oneself, others, and the world [52]. Considerable research findings, including ours, have demonstrated the positive relationship between character strengths and wellbeing across culture, lifespan, and population [25,26,32,53,54]. Given the same conditions, older people with high character strengths likely perceive difficult moments in life in a less negative manner than those with low character strengths.…”
Section: Discussionmentioning
confidence: 75%
“…A sample item is “I find the world a very interesting place” (curiosity). Several studies demonstrated the good psychometric properties of the German version of the VIA-IS (e.g., Proyer and Ruch, 2009; Müller and Ruch, 2011; Güsewell and Ruch, 2012; Buschor et al, 2013; Proyer et al, 2013a; Martínez-Martí and Ruch, 2014). Internal consistencies in the present study ranged from α = 0.71 to 0.92 (median = 0.80).…”
Section: Methodsmentioning
confidence: 99%
“…One of the criteria for the inclusion of a strength in the classification was that it should contribute to individual fulfillment . Broad evidence has been collected over the past years from correlational studies (using different methods for the assessment of strengths including peer-reports and a broad variety in the samples studied) that the VIA-strengths are positively associated with different indicators of subjective well-being (see Park et al, 2004; Park and Peterson, 2006a,b; Peterson et al, 2007; Ruch et al, 2007, 2010, 2014a,b; Khumalo et al, 2008; Brdar et al, 2011; Proyer et al, 2011, 2013a; Gander et al, 2012; Güsewell and Ruch, 2012; Littman-Ovadia and Lavy, 2012; Buschor et al, 2013; Martínez-Martí and Ruch, 2014; Azañedo et al, 2014; Berthold and Ruch, 2014). When Peterson and Seligman (2004) introduced the VIA-classification, they argued that strengths are malleable and, therefore, could be used for strengths-based interventions 1 targeting well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Por su parte, Martinez-Marti & Ruch, (2014) publicaron que las fortalezas que más se relacionan con el bienestar son: inteligencia social y perseverancia; en otra instancia Buschor, Proyer, & Ruch, (2013) evidenciaron que la curiosidad, amor por el conocimiento y la gratitud tienen fuerte impacto en el bienestar psicológico; Proyer et al (2011) han informado fuertes correlaciones del humor con el bienestar psicológico; así como Park et al (2004) demostraron que la gratitud es una de las fortalezas más valiosas en la varianza del bienestar.…”
Section: Discussionunclassified